Development of Language Creativity through Linguistic Innovation in Learning Indonesian Language at Al Washliyah Tembung Primary School - Sihombing, Evi Ariyanti Marlina; Lubis, Aminah; Silalahi, Yulianda Ghrace; Adisaputera, Abdurrahman; Ansari, Khairil (Budapest International Research and Critics University, 2024)
This research aims to explore and describe the application of linguistic innovation in increasing students' language creativity at SD Al Washliyah Tembung in the context of Indonesian language learning in the classroom. This research method uses a qualitative approach with a focus on collecting data through classroom observations, interviews with teachers, and document analysis. Various linguistic innovations, including word creation, language games, associative thinking, exploration of dialects and language variations, sociolinguistic simulations, as well as collaborative literary works, are applied in the learning process. The results of the research show that the application of linguistic innovation can stimulate students' creativity at SD Al Washliyah Tembung in language, expand vocabulary, improve communication skills, and deepen understanding of language diversity. The implications of these findings provide valuable insights for educational practitioners about the importance of adopting innovative approaches in language learning to stimulate students' creativity and enrich their learning experiences